Daya Antibakteri Ekstrak Etanol Kulit Manggis (Garcinia Mangostana Linn.) Terhadap Bakteri Porphyromonas Gingivalis - Ajie Nuperdanna Sriyono, Rexsy; Andriani, Ika (Universitas Muhammadiyah Yogyakarta, 2013)
Based On The Indonesian Household Health Survey, The Prevalence Of Periodontal Disease Reaches 60 % In Indonesian Community. One Of The Pathogen Bacteria That Involved In Periodontitis Is Porphyromonasbgingivalis. Mangosteen (Garciniamangostana Linn.) Is The Plants That Have The Ability To Inhibit Or Kill Porphyromonasgingivalis Is Which Is Its Skin Extract Contains Active Compounds Such As Saponins , Flavonoids And Tannins. The Purpose Of This Study Was To Examine The Antibacterial Effect Of The Ethanol Extract Of Mangosteen Peel (Garciniamangostana Linn.) Against The Growth Of Porphyromonasngingivalis .Mangosteen Peel Extract Was Obtained By Maceration Method Using Ethanol Solvent . The Antibacterial Activity Assays Was Used To Investigate The Effectivity Of Ekstract Ekstract Mangosteen Were Used Concentration Of 50 % , 25 %, 12.5 %, 6.25 %, 3.125 %, 1.563 %, 0.781 %, 0.39 %,0.195 %, And 0.0975 %. Results Showed That Extracts Of Mangosteen Peel Garciniamangostana Linn.)Has Mic And Mbc Against Porphyromonasgigngivalis Each At A Concentration Of 25 % And 50 % .